Interdisciplinary Actions in the Physical and Educational Care of Older Adults in the Community - Pereira, Francisco Barbosa; Martínez, Carlos Manuel Fuentes; Suzarte, Julio César Pérez; Pereira, João Dias; Santana, Giraldo Machuat (CV. Green Publisher Indonesia, 2025)
The complexity of aging processes requires integrated care that transcends disciplinary boundaries. This study addresses the research problem: